Climate change reporting for rural broadcasters Engaging rural media for community mobilization on climate-smart agriculture in the Philippines - Cruz, A.; Navarro, Rex; Tabing L (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2016)
To kick off a pilot rural radio campaign on climate-smart agriculture (CSA), three seminar workshops titled “Climate Change: iBroadkas Mo!”, for rural broadcasters in the Philippines were organized by the Philippine Federation of Rural Broadcasters (PFRB), with the support of the CGIAR Research Program on Climate Change, Agriculture and Food Security in Southeast Asia (CCAFS-SEA). Participants for these seminar workshops were member broadcasters of the PFRB in strategic regions of the Philippines. Moreover, it was also attended by other media practitioners and government information officers from around the area. Participants to the workshops were familiarized with climate change concepts to improve their capacities in broadcasting climate-related issues and concepts to their audiences. The total number of participants for the whole series was 180 which included 147 practicing broadcasters, 19 government information officers and five staff members from the PFRB. Presentations and discussions during the workshops focused on CSA and techniques and practices for broadcasting climate-related issues effectively. Participants were asked to produce prototype scripts and radio programs, which may include two radio spots, a short interview or voice clips of experts, on CSA as their output for the workshops. The PFRB campaign on climate change, which was launched during the workshops, will engage the services and programs of 150 rural broadcasters in the Philippines in mobilizing the rural sector (particularly farmers, fisherfolk and rural women) and advocating the practice of climate smart agriculture. Members of the PFRB and their network of community radio practitioners will be provided with ready-to-be-aired interviews and scripts on climate-smart agriculture. The broadcast materials will be produced in the languages of selected pilot regions. To motivate broadcasters, a reward and incentive system based on listenership and impact shall be put in place.